1993
DOI: 10.1161/01.cir.87.3.893
|View full text |Cite
|
Sign up to set email alerts
|

Regional ischemic 'preconditioning' protects remote virgin myocardium from subsequent sustained coronary occlusion.

Abstract: Brief episodes of ischemia in one vascular bed protect remote, virgin myocardium from subsequent sustained coronary artery occlusion in this canine model. These data imply that preconditioning may be mediated by factor(s) activated, produced, or transported throughout the heart during brief ischemia/reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
791
2
29

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,197 publications
(832 citation statements)
references
References 25 publications
10
791
2
29
Order By: Relevance
“…In the early 1990s, Przyklenk et al [8] proposed the concept of remote ischemic preconditioning. In their study, brief ischemia of the remote circumflex artery provided protection to ischemic myocardium from subsequent sustained left anterior descending artery occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, Przyklenk et al [8] proposed the concept of remote ischemic preconditioning. In their study, brief ischemia of the remote circumflex artery provided protection to ischemic myocardium from subsequent sustained left anterior descending artery occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…rIPC was first demonstrated in cardiac tissue in which brief episodes of myocardial ischemia and reperfusion applied to one vascular territory reduced the infarct size of the adjacent tissue that had not undergone any preconditioning. 2 rIPC has primarily been applied to the myocardium as a target organ, but subsequent studies showed that brief ischemia induced in nontarget tissue, most commonly in the limb or arm, confers protection at a remote site such as the brain, lung, kidney, intestine, or skeletal muscle. [3][4][5] rIPC causes a similar degree of tissue protection, as does IPC.…”
mentioning
confidence: 99%
“…In 1993, Pryzklenk and colleagues (52) made the intriguing observation that the preconditioning effect elicited by brief ischaemia in the circumfl ex artery territory could actually be manifested in myocardium supplied by the left anterior descending artery territory, indicating for the fi rst time that protection could be conveyed from one region of the heart to another. This concept has been further evolved and developed to extend to organs and tissue distant from the heart such as the kidney, small intestine, liver, and the limbs, such that brief episodes of ischaemia and reperfusion applied to these organs or tissue have been reported to protect against myocardial infarction -a phenomenon termed remote ischaemic preconditioning (RIPC) (reviewed in).…”
Section: Remote Ischaemic Preconditioning: Giving Your Right Arm To Pmentioning
confidence: 99%